Sites of Memory in Andalusia. A way to go - Barrera Becerra, Eduardo; Giráldez Díaz, Fco. Javier; Melero Vargas, Miguel Ángel (Huarte de San Juan. Geografía e Historia, 2020)
The text tries to approach the actions related to the public management of the places of memory of the Civil War and Francoism in Andalusia. In the first place, we review the repressive reality that Francoism implemented in the region with the highest number of victims in Spain and that gave rise to a series of spaces related to the memory of the victims. For this, we examine the specific regulations that have regulated them in Andalusia and that have been a benchmark for other regions, and the basis on which more than fifty places of memory have been officially declared by the Andalusian Government. The importance of these places, their heterogeneity and significant examples are also the subject of this article made from the experience in the elaboration of the norms and management of these spaces by their authors in the defunct General Management of Democratic Memory of the Government of Andalusia.
Keywords: Sites; Memory; victims; repression; Andalusia